(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to diagnose changes psychomotor children of both sexes, aged 7 years enrolled in two different schools of the network of municipal education located in the city of Manaus. We evaluated 62 children from school A, with 37 girls and 25 boys and 63 from school B, 34 girls and 29 boys. All subjects were assessed by TGMD (Test of Gross Motor Development, Ulrich, 1985) which assesses the motor performance of motor skills of locomotion and object control. The data were presented by descriptive analysis, mean and standard deviation. The data showed a normal distribution we used Student’s T test for independent samples to compare genders, for non-normal distribution the Krumam Wallis test, significance level p <0.05. The results suggest that: (1) boys and girls of both schools are older motor than chronological age, which is seven years for all skills assessed, (2) To skills locomotion girls and boys from the school did not detect the difference significant, since the school was no difference B, boys are older than the motor of the girls, (3) For the management skills of objects girls and boys from the school showed similar results, with no difference. The school B showed a difference, boys achieved better results, (4) When comparing schools was no difference for females, the results of the girls are lower than B for the skills assessed. The boys showed similar results. Among the objectives of physical education classes is to give children contact with a wide variety of experiences of movement. For this to happen we need the lessons are well planned and executed, thus ensuring the development and learning fundamental skills.